The inclusion of international tourists: developing the translator-client relationship (Altre Modernità, 2019)
Recent interdisciplinary research bridging Translation and Tourism Studies has often noted that a source text written for domestic tourists may well, if just closely translated, not meet the needs of an international tourist audience. As a result translators may prefer to depart from the source text in order to produce a target text which includes its international audience. This implies a shift in the translator’s role from someone who facilitates communication on a client’s behalf to someone who in part defines the communication. But even if clients are committed to inclusion, the need for this shift may not be evident to them, especially when their level of cultural and linguistic awareness is weaker than that of the translator. Such gaps in awareness create challenges for translators. This article clarifies these challenges and describes intercultural skills to help meet them. These can be divided into three broad areas— skills in delivering intercultural education, communication skills for arriving at informed consent for a translation/adaptation strategy and skills in context-relevant ethical reasoning. Such skills, it is argued, can be incorporated into translator training programmes, especially those with courses on specialist discourses like tourism discourse. Developing such competences, it is argued, can empower translators to produce more inclusive texts using bold adaptation or translation strategies knowing they have negotiated with clients ethically.